Splenectomy Is Modifying the Vascular Remodeling of Thrombosis. Issue 1 (28th February 2014) - Frey, Maria K.; Alias, Sherin; Winter, Max P.; Redwan, Bassam; Stübiger, Gerald; Panzenboeck, Adelheid; Alimohammadi, Arman; Bonderman, Diana; Jakowitsch, Johannes; Bergmeister, Helga; Bochkov, Valery; Preissner, Klaus T.; et al.
Abstract : Background: Splenectomy is a clinical risk factor for complicated thrombosis. We hypothesized that the loss of the mechanical filtering function of the spleen may enrich for thrombogenic phospholipids in the circulation, thereby affecting the vascular remodeling of thrombosis. Methods and Results: We investigated the effects of splenectomy both in chronic thromboembolic pulmonary hypertension (CTEPH), a human model disease for thrombus nonresolution, and in a mouse model of stagnant flow venous thrombosis mimicking deep vein thrombosis. Surgically excised thrombi from rare cases of CTEPH patients who had undergone previous splenectomy were enriched for anionic phospholipids like phosphatidylserine. Similar to human thrombi, phosphatidylserine accumulated in thrombi after splenectomy in the mouse model. A postsplenectomy state was associated with larger and more persistent thrombi. Higher counts of procoagulant platelet microparticles and increased leukocyte–platelet aggregates were observed in mice after splenectomy. Histological inspection revealed a decreased number of thrombus vessels. Phosphatidylserine‐enriched phospholipids specifically inhibited endothelial proliferation and sprouting. Conclusions: After splenectomy, an increase in circulating microparticles and negatively charged phospholipids is enhanced by experimental thrombus induction. The initial increase in thrombus volume after splenectomy is due to platelet activation, and the subsequent delay of thrombus resolution is due to inhibition of thrombus angiogenesis. The data illustrate a potential mechanism of disease in CTEPH.